miR-486 Promotes Capan-2 Pancreatic Cancer Cell Proliferation by Targeting Phosphatase and Tensin Homolog Deleted on Chromosome 10 (PTEN) - Xia, Lu; Song, Meiyi; Sun, Mengxue; Chen, Wei; Yang, Changqing (Frontiers in Genetics, 2019)
Introduction: Pancreatic cancer is one of the most common malignant digestive system tumors. Current treatment options for pancreatic cancer cannot achieve the expected curative effect. MicroRNAs (miRNAs and miRs) participate in many biological and pathological processes. miR-486 has been reported to be involved in diverse types of malignant tumors; however, its role in pancreatic cancer remains unclear. Material and Methods: miR-486 mimics and inhibitors were transfected into Capan-2 cells to increase or decrease the expression of miR-486. Western blot was used to detect protein expression levels. EdU proliferation assay and flow cytometry were applied to identify changes in proliferation. In combination with a PTEN overexpression plasmid, miR-486 mimics were used to determine whether PTEN upregulation abolished the proliferative effect of miR-486. Results: Overexpression of miR-486 promoted proliferation and cell cycle progression of Capan-2 cells. Conversely, the proliferation and cell cycle of Capan-2 cells were attenuated after inhibition of miR-486. Using a combination of bioinformatics and Western blot analysis, PTEN was identified as a downstream target gene of miR-486. The effect of miR-486 on Capan-2 cell proliferation could be abolished by PTEN overexpression. Conclusions: miR-486 promotes the proliferation of Capan-2 cells by targeting PTEN. Inhibition of miR-486 might be a novel therapy for pancreatic cancer.